Anisotropic Materials for Skeletal‐Muscle‐Tissue Engineering. Issue 48 (16th November 2016) - Jana, Soumen; Levengood, Sheeny K. Lan; Zhang, Miqin
Abstract : Repair of damaged skeletal‐muscle tissue is limited by the regenerative capacity of the native tissue. Current clinical approaches are not optimal for the treatment of large volumetric skeletal‐muscle loss. As an alternative, tissue engineering represents a promising approach for the functional restoration of damaged muscle tissue. A typical tissue‐engineering process involves the design and fabrication of a scaffold that closely mimics the native skeletal‐muscle extracellular matrix (ECM), allowing organization of cells into a physiologically relevant 3D architecture. In particular, anisotropic materials that mimic the morphology of the native skeletal‐muscle ECM, can be fabricated using various biocompatible materials to guide cell alignment, elongation, proliferation, and differentiation into myotubes. Here, an overview of fundamental concepts associated with muscle‐tissue engineering and the current status of muscle‐tissue‐engineering approaches is provided. Recent advances in the development of anisotropic scaffolds with micro‐ or nanoscale features are reviewed, and how scaffold topographical, mechanical, and biochemical cues correlate to observed cellular function and phenotype development is examined. Finally, some recent developments in both the design and utility of anisotropic materials in skeletal‐muscle‐tissue engineering are highlighted, along with their potential impact on future research and clinical applications. Abstract : Muscle‐tissue‐engineering approaches are reviewed, focusing on anisotropic matrices, including micropatternered substrates, and aligned microporous and aligned fibrous scaffolds. Challenges associated with engineering aligned matrices are highlighted and correlation of scaffold topographical, mechanical, and biochemical cues to cellular function and myogenic phenotype development is discussed.